A development in solar desalination system with flashing of solar heated water - Hemin Thakkar; Hitesh Panchal; D.D.Mevad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Solar still was successfully used for the desalination of saline water in many arid and oceanic regions of the world. But the yield of solar still was found very low and fluctuating. The new develop system with the flashing of solar-heated water is found possible during the study of flashing of hot water in many thermal processes used during the chemical and pharmaceutical processes. A compact and effective desalination system using solar energy had designed during the research work from the design reviews collected from flashing hot water devices used in many thermal processes. The compact flash chamber and flash steam condenser are critical components developed for the novel desalination system using locally available materials during the research work. In present experimental work a flash chamber is designed for flashing of solar heated water. Experimental work shows that by increasing the mass flow rate of water from 0.01 kg/sec to 0.02 kg/sec the distillate output of water could be increased with higher temperature of water. It shows that around 38% of higher distillate output in water could be achieved with development of new system.